Purple Flat Top : in pursuit of a place - Nisbet, Jack, 1949- (Sasquatch Books, 1996)
When a mining claim on a crumbling cliff of burnt-rose quartzite lured naturalist Jack Nisbet to the northeastern corner of Washington State in 1970, he began a search for an understanding of that open country through stories about the people who lived there and the everyday events he shared with them. Together, these vivid, engaging, and subtly humorous stories evoke the essence of this place.